The Influence of Household Types on Food and Grocery Store Choices - 김만근 (한국농촌경제연구원, 2018)
This study examines the effect of household type on food and grocery store choices using the 2016 KREI Consumer Behavior Survey for Food (CBSF) data. This study further investigates factors (e.g., socio-economic characteristics, consumer capacities, and store attributes), in relation to food and grocery store choices. There exist significantly different store choices among the household types. The marginal effects from the multinomial logit model show that one-person households are more likely to choose supermarkets as their primary food and grocery stores. In contrast, relatively young (age under 45) multi-person households are more likely to shop their food and groceries in large discount stores. Both elderly (age 65 and up) one-person and multi-person households prefer to go to supermarkets as well as traditional markets. Except for elderly households, all the households are less likely to shop in traditional markets. The implications for growing one-person and elderly households are discussed.
Keywords: 식품시장; 고령자; 1인 가계; 정책; 식료품 판매점; food market; older adults; one-person households; policy; grocery store